IT BUSSINESS : AT A GLANCE CLOUD LEARNING SYSTEM IN EF BANDARLAMPUNG - Arnes Yuli Vandika; Ruri Koesliandana; Dina Ika Wahyuningsih (UBL, 2016)
In the learning In the use of technology teaching techniques in English for now is widely used for business, In large enterprises, the Cloud can lower costs, this is because companies do not need to buy a computer with a high specification of which to manipulate and store data, reducing the cost of hardware and software maintenance, no need to buy separate software for each PC in the company.Users do not need to bother to pay or download the upgrade application is used, it is because every time you log into the Cloud app will update automatically. The experiments show that learners who Adopted a situated and reading-based English learning system exhibitedhigher quality performance than conventional Reviews those who Adopted learning systems and Information Communication Technology (ICT). And, the performance ofLearners who utilized the learning support system with a reading guidance mechanism was of higher quality thanMerely that of learners who utilized a simple situated learning system.